Control of Dichotomic Innate and Adaptive Immune Responses by Artery Tertiary Lymphoid Organs in Atherosclerosis - Weih, Falk; Gräbner, Rolf; Hu, Desheng; Beer, Michael; Habenicht, Andreas J. (Frontiers in Physiology, 2012)
Tertiary lymphoid organs (TLOs) emerge in tissues in response to nonresolving inflammation such as chronic infection, graft rejection, and autoimmune disease. We identified artery TLOs (ATLOs) in the adventitia adjacent to atherosclerotic plaques of aged hyperlipidemic ApoE-/- mice. ATLOs are structured into T cell areas harboring conventional dendritic cells (cDCs) and monocyte-derived DCs (mDCs); B cell follicles containing follicular dendritic cells (FDCs) within activated germinal centers; and peripheral niches of plasma cells. ATLOs also show extensive neoangiogenesis, aberrant lymphangiogenesis, and high endothelial venule (HEV) neogenesis. Newly formed conduit networks connect the external lamina of the artery with HEVs in T cell areas. ATLOs recruit and generate lymphocyte subsets with opposing activities including activated CD4+ and CD8+ effector T cells, natural and induced CD4+ T regulatory cells (nTregs; iTregs) as well as B-1 and B-2 cells at different stages of differentiation. These data indicate that ATLOs organize dichotomic innate and adaptive immune responses in atherosclerosis. In this review we discuss the novel concept that dichotomic immune responses towards atherosclerosis-specific antigens are carried out by ATLOs in the adventitia of the arterial wall and that malfunction of the tolerogenic arm of ATLO immunity triggers transition from silent autoimmune reactivity to clinically overt disease.